2017
DOI: 10.1371/journal.pone.0169766
|View full text |Cite
|
Sign up to set email alerts
|

Obesity May Not Induce Dynamic Stability Disadvantage during Overground Walking among Young Adults

Abstract: Obesity has been related to postural instability during static standing. It remains unknown how obesity influences stability during dynamic movements like gait. The primary aim of this study was to investigate the effects of obesity on dynamic gait stability control in young adults during gait. Forty-four young adults (21 normal-weight and 23 obese) participated in this study. Participants walked five times at their self-selected gait speeds on a linear walkway. Their full-body kinematics were gathered by a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(59 reference statements)
1
12
0
1
Order By: Relevance
“…Furthermore, a shorter single support phase in combination with an increase in step time may be induced to establish a more stable double support phase more quickly and for a longer time [46]. increase in BMI, slower walking speeds, shorter steps and a longer double support phase are preferred in order to minimize the gross energy cost [45,[48][49][50]. Specifically, the slower walking speed lowers the mechanical work needed to redirect the CoM [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a shorter single support phase in combination with an increase in step time may be induced to establish a more stable double support phase more quickly and for a longer time [46]. increase in BMI, slower walking speeds, shorter steps and a longer double support phase are preferred in order to minimize the gross energy cost [45,[48][49][50]. Specifically, the slower walking speed lowers the mechanical work needed to redirect the CoM [49].…”
Section: Discussionmentioning
confidence: 99%
“…increase in BMI, slower walking speeds, shorter steps and a longer double support phase are preferred in order to minimize the gross energy cost [45,[48][49][50]. Specifically, the slower walking speed lowers the mechanical work needed to redirect the CoM [49]. The slower walking speed in combination with a shorter step length may explain the unchanged AP MoS, ensuring forward progression without increasing the risk of a backwards loss of balance [51].…”
Section: Discussionmentioning
confidence: 99%
“…Old age [36,37] and body mass associated with obesity [38] are both associated with reductions in stability. To offset this instability, older adults [11][12][13] and obese individuals [38] select conservative gait patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Old age [36,37] and body mass associated with obesity [38] are both associated with reductions in stability. To offset this instability, older adults [11][12][13] and obese individuals [38] select conservative gait patterns. In the current study, our participants spanned a large range of ages (18-75 years) and body weights (49-96 kg).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high body mass index (BMI) has an association with increased postural sway in obese [6,8], mainly in the medial-lateral (ML) direction for men and anteroposterior (AP) for women [8][9][10], and occurrence of falls in adults [11]. However, some studies reported no difference between obese and control group regarding the position of the center of pressure (COP) in static PB [12,13] and the dynamic gait stability [14]. Although these previous findings suggest that body weight is responsible for more than 50% of the variance of COP speed [5], it is not reasonable just to consider this anthropometric variable for explaining the PB in obesity.…”
Section: Introductionmentioning
confidence: 99%